A project-based approach to subtitler training - Szarkowska, Agnieszka (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
In this article I describe how a project-based approach can be implemented when training subtitlers. I present collaborative project-based work carried out at the Institute of Applied Linguistics, University of Warsaw, as part of an optional module on subtitling in the MA Programme in Translation. The project was conducted in cooperation with the Polish National Film Archive. As part of the project, students had to subtitle into English some Polish pre-World War II films. I describe the project, the structure and content of the course, the working methods, the assessment and the students’ feedback. Finally, I discuss the advantages and disadvantages of a project-based approach compared to traditional subtitling teaching models within the higher education framework.